The relationship of riparian vegetation guilds to alluvial groundwater, flood disturbance, and the provisioning of bird habitat along rivers in the Colorado River basin - Cubley, Erin Susan, author; Cooper, David J., advisor; Merritt, David M., committee member; Wohl, Ellen E., committee member; Kampf, Stephanie, committee member (Colorado State University. Libraries, 2020)
Riparian ecosystems provide essential services including flood mitigation, organic matter and energy, nutrient cycling, and wildlife habitat with their structure and function strongly influenced by fluvial processes and shallow groundwater. Riparian areas across the world have been degraded by land development and the alteration of streamflow by dams, diversions, dikes, and groundwater pumping. Climate change will further stress riparian ecosystems and the Colorado River is predicted to experience the largest decrease in streamflow of the major basins in the western US. Changes in the patterns of stream flow can result in the alteration of plant communities, physical structure, and overall ecosystem functioning. Efforts to understand how plant species are distributed along hydrologic gradients in riparian zones have focused on individual species. The use of vegetation guilds, groups of plants with similar functional traits, may be useful in generalizing plant responses to streamflow alterations across rivers. The identification of trait-based guilds with member species that respond similarly to stressors common along rivers directly links plant performance to environmental processes. The range of traits within a vegetation guild can also help explain how functionally similar species contribute to vegetation structure and heterogeneity that supports habitat for wildlife, including birds that rely on riparian ecosystems for breeding, foraging, nesting, and migration. In Chapter 1, I investigate the relationship between riparian vegetation guilds, vegetation structure, and bird habitat along the Verde River in Arizona. Five woody and seven herbaceous guilds were classified using a suite of functional traits including specific leaf area, potential rooting depth, and seed mass. Bird abundance, diversity, and richness were best predicted by the cover of the tall tree guild dominated by Salix gooddingii and the drought tolerant shrub guild dominated by Prosopis velutina. These results highlight the need to conserve not only riparian forests, but shrubs that provide food and nesting sites for bird species that prefer low-statured vegetation. In Chapter 2, I assess the connection between Verde River streamflow, alluvial groundwater, and the occurrence of woody and herbaceous riparian vegetation guilds. Groundwater depth was strongly controlled by streamflow changes and tall tree guild members were more likely to occur where groundwater was less than 2.5 m from the floodplain surface. The distribution of woody vegetation guilds was explained by groundwater depth and flood exceedance probability, but hydrologic attributes only explained variation in occurrence of two herbaceous guilds. Simulations of lowered groundwater indicate that presences of tall trees, short trees, and flood tolerant shrubs will decrease while drought tolerant shrubs and generalist shrubs will increase along the Verde River. In the final chapter I determine if riparian vegetation guilds occupy similar habitat controlled by groundwater depth and flooding in river basins with different climate and streamflow regimes. I compared trait composition of guilds in two study regions, Arizona and Colorado, and assessed how guild occurrence could change under conditions of lowered inundation exceedance probability and deeper groundwater levels using simulation modeling. I compared vegetation guilds along the Verde River with those along the Dolores and San Miguel Rivers in Colorado and found that the structural dominant guilds were different in each study region. Flood tolerant shrubs dominated at high elevation reaches in Colorado while lower elevation reaches were characterized by a mix of flood tolerant shrubs, tall trees, and generalist shrubs. Tall trees were the dominant guild along the Verde River. Two vegetation guilds had similar trait composition between study regions, but my results imply that hydrologic processes supporting them are different. Hillslope groundwater contributions and higher average annual precipitation at higher elevation reaches in Colorado maintained high floodplain groundwater levels that varied less compared to lower elevation reaches in Colorado and the Verde River. Riparian vegetation zonation was less distinct at Colorado study reaches than Arizona. Simulations of lowered groundwater levels indicate declines in dominant riparian vegetation guilds within both study regions, but not all study reaches. A water table decline of greater than 0.50 m is predicted to decrease tall trees, short trees, and flood tolerant shrubs in Arizona while in Colorado, Uravan and Bedrock were the only reaches modeled to experience a decrease in flood tolerant shrubs. Overall, riparian guilds with narrower groundwater ranges were predicted to decrease the most and the magnitude of change was higher in response to lowered groundwater levels compared to altered flood regimes All study reaches along the Verde River and the Uravan study reach on the San Miguel were predicted to experience expansions of the generalist shrub guild in response to altered hydrologic condition. The following dissertation contributes to our understanding of plant distributions in riparian areas, hydrologic thresholds, and hydrologic variability within and between rivers. We found that riparian vegetations may be more transferable within regions while plant-hydrologic relationships between regions may be dissimilar due to climate, valley morphology, groundwater sources, and flow regimes.
Keywords: plant distribution; Verde River; flow response guild; wildlife habitat; riparian